(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Gifardi MD, Sutardi LN, Farida WR, Prawira AY, Agungpriyono S. 2022. Antibacterial activity of Sunda porcupine quill extract (Hystrix javanica) against Staphylococcus aureus. Biodiversitas 23: 4355-4360. The Sunda porcupine (Hystrix Javanica) is a rare mammal with quill-like hair covering its body. Because the Sunda porcupine has extensive sebaceous glands, the neutral carbohydrate content is well-distributed and is known to have excellent wound healing. In addition, the high acid content of porcupine quills is believed to influence wound healing by inhibiting the growth of bacteria that cause infection on the skin. This study aims to demonstrate the antibacterial activity of the Sunda porcupine quill extract, determine the antibacterial ability of the Sunda porcupine quill extract, and examine the influence of concentration variations on the growth inhibition of Staphylococcus aureus bacteria. Well-diffusion testing of the antibacterial activity of the Sunda porcupine quill extract (so that it is well-diffusion). The test findings demonstrated that the Sunda porcupine quill extract possessed antibacterial properties. The antibacterial activity of porcupine quill extract was indicated by the diameter of the clear zone (inhibition zone) based on the variation of the extract concentration used, namely 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, 1.5625%. The antibacterial activity of the Sunda porcupine quill extract was seen at concentrations of 100%, 50%, and 25%, with the average diameter of the clear zone being 14.88 mm ± 2.43; 12.24 mm ± 2.59; and 12.74 mm ± 3.69. The test results showed an effect of variations in the concentration of Sunda porcupine quill extract on the diameter of the clear zone (P??=0.05) based on the one-way ANOVA test. Sunda porcupine quill extract with concentrations of 100%, 50%, and 25% is included in the category of strong antibacterial so that it can be used as an antibacterial agent.